Pembuatan Aplikasi Sistem Informasi Akuntansi dan Price Calculator pada Perusahaan Manufaktur CV Berkat Anugerah - Hermawan Hadi Saputra; Yulia -; Andy Setiabudi (Jurnal Infra, 2015)
CV Berkat Anugerah is an individual manufacturing company which focused in lathe workshop. The current system used is a manual system, which makes difficult for storing and processing data. The production process based on customer’s request. Each order are custom-made so the selling price is different for each order. Selling price is affected by cost of goods manufactured. The estimation for cost of goods manufactured is a problem faced by the company.Based on background issues that occur, the author create an accounting information system and price calculator application. The accounting information system is used for daily-bases operation. Price calculator application is used to help the calculation process for cost of goods manufactured. These application is made using Microsoft Visual Studio 2010 as programming language and SQL Server as database. Job Order Costing method is used for calculating cost of goods manufactured.The result of application’s testing are accounting information system helps the process of storing and processing transactional data so that can generate an accurate financial statements. Price calculator helps making an accurate cost of goods manufactured calculation process, so that company can gain the best profit for each order.